PENDEKATAN PENDIDIKAN YANG FLEKSIBEL DAN PROGRESIF - Yaldi, Yusri; Hanani, Silfia; Sesmiarni, Zulfani; Salim, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Islamic boarding schools have long been traditional educational institutions in Indonesia that play an important role in forming character and religious knowledge for students. However, in facing the challenges of the modern era, a flexible and progressive educational approach is needed to maintain the relevance and competitiveness of Islamic boarding schools in producing individuals who are ready to face the complexities of the contemporary world. This research aims to explain the flexible and progressive educational approach in Islamic boarding schools, as well as its impact on the students' learning experience. This research method involves literature study, interviews, and participant observation in several Islamic boarding schools that apply this approach. The research results show that the flexible and progressive educational approach in Islamic boarding schools combines elements of traditional education with modern educational methodology and content. This is reflected in the provision of a curriculum that includes religious education, general science and practical skills, as well as an emphasis on critical and creative development of students. The impact of this approach can be seen in increasing learning motivation, critical thinking skills, and student independence in managing their knowledge and experience. Apart from that, this approach also opens up opportunities for Islamic boarding schools to play an active role in building relationships with society and the industrial world, thereby expanding the reach and impact of Islamic boarding school education in a broader social context.